Management of Partial Necrosis of Submental Flap – A Case Report - Mukul, Sailesh Kumar; Rashid, Sibgutulah; Gupta, Vyakhya Akhileshkumar; Mishra, Rajni (Journal of Orofacial Research, 2025)
We report a case of a 68-year-old male with recurrent unicystic ameloblastoma involving the anterior mandible who underwent anterior marginal mandibulectomy and reconstruction with a submental artery island flap. Despite uneventful intraoperative planning, the patient developed partial distal flap necrosis postoperatively. Given the patient’s age and systemic comorbidities, conservative wound care was chosen over secondary surgical intervention. Gradual healing was achieved without functional or aesthetic compromise. This case highlights the submental flap’s utility in elderly patients and emphasizes the importance of early identification and non-surgical management of flap complications.